Influence of oxytocin on emotion recognition from body language: A randomized placebo-controlled trial - Bernaerts, Sylvie; Berra, Emmely; Wenderoth, Nicole; Alaerts, Kaat (Psychoneuroendocrinology, 2016)
•We examined effects of intranasal oxytocin (OT) on ‘reading’ emotional body language.•‘Reading’ emotional body language from point light displays as a novel paradigm.•Identical and novel stimuli were presented pre- and post-OT administration.•OT enhanced bodily emotion recognition when novel stimuli were used post-OT treatment.•Effect was masked when identical stimuli were presented pre- and post-OT treatment. The neuropeptide ‘oxytocin’ (OT) is known to play a pivotal role in a variety of complex social behaviors by promoting a prosocial attitude and interpersonal bonding. One mechanism by which OT is hypothesized to promote prosocial behavior is by enhancing the processing of socially relevant information from the environment. With the present study, we explored to what extent OT can alter the ‘reading’ of emotional body language as presented by impoverished biological motion point light displays (PLDs). To do so, a double-blind between-subjects randomized placebo-controlled trial was conducted, assessing performance on a bodily emotion recognition task in healthy adult males before and after a single-dose of intranasal OT (24 IU). Overall, a single-dose of OT administration had a significant effect of medium size on emotion recognition from body language. OT-induced improvements in emotion recognition were not differentially modulated by the emotional valence of the presented stimuli (positive versus negative) and also, the overall tendency to label an observed emotional state as ‘happy’ (positive) or ‘angry’ (negative) was not modified by the administration of OT. Albeit moderate, the present findings of OT-induced improvements in bodily emotion recognition from whole-body PLD provide further support for a link between OT and the processing of socio-communicative cues originating from the body of others.